Social media influencers: effects of followers' behavior and response to influencers - Anugerah Trisatryo; Nurdin Sobari (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
Against the backdrop of the growing prevalence of social media influencers shaping consumer behavior, this study aims to analyze the sequential influence of stimuli in the form of product posts and beauty influencers on social media influenced various organisms so that responses in the form of intentions to follow beauty influencer accounts, imitate the lifestyle of beauty influencers, and recommend beauty influencers. Researchers use quantitative method. The targeted respondents are Generation Z and millennial individuals in Indonesia who are over 18 years old and follow at least one influencer on Instagram. The minimum sample desired for this study was 260 respondents. Data analysis is carried out using the Partial Least Square-Structural Equation Model (PLS-SEM) method. The results showed that product-influencer compatibility has a positive influence on followers' perceptions of ad posts, followers' perceptions of the credibility of influencers, and influencers themselves. The perception of ad posts also has a positive influence on followers' perception of influencers' credibility and perceptions of follower behavior toward influencers. Likewise, the credibility of influencers has a positive influence on follower behavior towards influencers and followers' intentions to keep following accounts, imitating influencers, and recommending influencers to others. The behavior of followers towards influencers has a positive effect on the intention of followers to keep following accounts, imitating influencers, and recommending influencers to others.